THE INFLUENCE OF INTERNSHIP EXPERIENCE AND CAREER GUIDANCE ON STUDENT WORK READINESS: A QUANTITATIVE DESCRIPTIVE RESEARCH STUDY - Hakiki, Muhammad; Budiman, Ridho Dedy Arief; Firdaus, Muhamad; Astiti, Ayu Dewi (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2023)
This study aims to investigate the impact of internship experience and career guidance on job readiness of Vocational High School (SMK) students in Information and Communication Technology (ICT) in Muara Bungo. The research method used is descriptive quantitative research with a comparative causal approach (Expost Facto). Data collection was done through indirect communication techniques, direct communication techniques, and documentary studies, using instruments in the form of questionnaires and documentation. The population of this study were all XII grade students at SMK N 1 Muara Bungo. The sampling technique used was Propotional Random Sampling. Data analysis was carried out with the following steps: (1) descriptive analysis; (2) prerequisite test analysis includes normality test, linearity test, and multicollinearity test; (3) hypothesis testing through simple regression analysis and multiple regression analysis. The results showed that internship experience has an influence of 45.5% on the work readiness of vocational students in the field of ICT in Muara Bungo. Furthermore, career guidance has an influence of 35.5% on the work readiness of the same students. Furthermore, the results show that pre-service learning experience and career guidance together have an influence of 54.9% on the work readiness of vocational students in the field of ICT in Muara Bungo.